Al Shabaab as a transnational actor : a critical theoretical analysis - Reid, Gabrielle Paxton (Department of Political Studies, 2016)
The Somalia-based militant group, Al Shabaab, has conducted mass casualty transnational terrorist attacks and has become a regional security threat. In an effort to uncover the best explanation of the drivers behind the group's use of transnational terror, a critical analysis of Rational Choice Theory, Spill-over Conflict Theory and Regional War Complex Theory was conducted. Evaluating each theory according to whether its assumptions held true, the theory offered a parsimonious explanation of Al Shabaab's use of transnational terror which could be supported by at least three types of evidence, the strengths and weaknesses of each theory, with regard to explaining Al Shabaab's transnational terror were identified. The findings showed that Al Shabaab as a transnational actor should not be seen as a linear transformation of the group, moving outwards from Somalia, but connected to an interlinked web between countries in the Horn of Africa, where domestic vulnerabilities such as political and socioeconomic marginalisation and a vulnerability to radicalisation allow for the cross-pollination of intent, and the capabilities to carry out attacks. As such, the regional and international interconnections captured by the Regional War Complex offered the best explanation of the drivers of Al Shabaab's use of transnational terror. Although Rational Choice Theory most clearly highlighted Al Shabaab's intent to transform from a domestic actor to a regional one, and the Spill-over Model showed that refugees could offer a recruitment source, it was the increased regional capabilities through the establishment of affiliates located outside of Somalia which gave the group the capacity to carry out transnational attacks and to operate as a transnational actor.